The role of HER family signalling in breast cancer - Kuruppu, Anchala (2016)
The HER family of receptors plays a major role in a variety of cancers including breast cancer. Several researchers have shown that HER family overexpression in breast cancer is a significant prognostic factor, especially for survival and relapse. Therefore, many therapeutics are being developed to test the impact of HER family blockade in breast cancer. Although numerous therapies have been developed, many have not been very successful in the clinic. This is often a consequence of cancer cells developing new mechanisms to activate HER family signalling indirectly through cross talk with compensatory pathways. Thus, it is vital to consider the biology of the HER signalling network to a greater extent, which includes RAS/MAPK, PI3K/AKT, mTOR, JAK/STAT, ER and AhR pathways and, also identify breast cancer patient populations that will benefit from specific targeted therapies that target these pathways.